People with higher interoceptive sensitivity are more altruistic, but improving interoception does not increase altruism. Issue 1 (December 2017) - Piech, Richard; Strelchuk, Daniela; Knights, Jake; Hjälmheden, Jonathan; Olofsson, Jonas; Aspell, Jane
Abstract People consistently show preferences and behaviors that benefit others at a cost to themselves, a phenomenon termed altruism. We investigated if perception of one's body signals – interoception - may be underlying such behaviors. We tested if participants' sensitivity to their own heartbeat predicted their decision on a choice between self-interest and altruism, and if improving this sensitivity through training would make participants more altruistic. Across these two experiments, interoceptive sensitivity predicted altruism measured through monetary generosity. Improving interoceptive sensitivity did, however, not lead to more altruistic behaviour. We conclude that there is a unique link between interoception and altruistic behaviour, likely established over an individual's history of altruistic acts, and the body responses they elicit. The findings suggest that humans might literally 'listen to their heart' to guide their altruistic behavior.